Anesthesia Simulator - Case 5 - Anaphylactic Reaction - Howard Schwid (Association of American Medical Colleges, 2009)
Abstract This resource is a case-based simulation on anaphylactic reaction. It features a 22-year-old healthy male presenting for appendectomy. He has a history of hay fever and a penicillin allergy, so there is a slightly increased risk for an allergic reaction. The patient may also be somewhat dehydrated and have an increased risk of aspiration with his acute abdomen; students must become adept at the differential diagnosis of hypotension under anesthesia. Anaphylactic reaction must be suspected in any patient with refractory hypotension. Other signs of anaphylactic reaction exhibited in this patient include tachycardia, bronchospasm, hypoxia, periorbital edema, and cutaneous flushing. Students must treat aggressively by securing the airway, ventilating with 100% oxygen, rapidly administering intravenous fluids, and appropriately providing boluses of epinephrine. Anesoft Anesthesia Simulator software is required to run the case simulation without any modifications. The use of the inexpensive Anesoft screen-based anesthesia simulator program was shown to improve response to simulated emergencies as much as mannequin-based simulators.